Impact of temporal bone dissection on the understanding anatomy of the ear among medical students - Prasad, K. C.; K., Prathyusha; Maruvala, Shreeharsha; T. R., Harshita; Gopi, Indu Varsha; K. R., Sumanth (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
The aim was to study the impact of temporal bone dissection demonstrations on understanding anatomy of the ear among medical students. During a period of six months from October 2017 to March 2018, 10 cadaveric temporal bones dissections were demonstrated using ZEISS microscope and in the presence of medical students headed by a Consultant Otolaryngologist in the department of ENT, Sri Devaraj URS Medical College and Research Centre, Kolar. Anatomy of the middle ear and inner ear and various operative procedures were demonstrated. The students were divided into 2 groups. Group I comprised students who attended the temporal bone dissection and Group II included those who didn’t attend dissection. After the session both the groups were assessed by the consultant. Scores were given to the group individuals based on the ability to answer the questions. 10 Temporal bone dissections were demonstrated in 6 months period to medical students who were divided into 2 groups based on their attendance of the demonstration. The students of both groups were assessed. Scores were given by Likert scale-5point scale question. The results of our study proved that those students who attended the temporal bone dissection (Group-I) had better understanding of the anatomy and operative procedures of the ear as compared to students in group II. Demonstration of temporal bone dissection to the medical students had a good impact on their understanding of the three dimensional anatomy of the ear.